Teletrabalho e desconexão : a saúde psicológica do trabalhador em estudo comparado Brasil e Argentina - Moreira, Laura Medina Martins (2022)
The present study, linked to the research line of Law, Science, Technology & Innovation, of the Graduate Program in Law of the Pontifical Catholic University of Rio Grande do Sul, seeks to analyze, from the Argentine legislative model, arising through the Law nº 27.555/20, ways to promote disconnection and, consequently, guarantee the psychological health of teleworkers. We highlight the contractual model of telework and its legal bases in Brazil and Argentina, their differences, based on theoretical, jurisprudential and legal assumptions, to promote the analysis in a comparative perspective, identifying and facing the problems arising from the implementation of telework as a matter of urgency, resulting from the crisis that occurred through the COVID-19 pandemic. Investigates doctrinal, legal and jurisprudential positions regarding the right to disconnect. It also verifies if disconnection is inserted as a fundamental right and if it is possible to guarantee it in telework. Identifies the advances in Argentine legislation and how they can help Brazil, in particular the constant changes in Bill Nº, 5.581/20, in the topic referring to the psychological health of teleworkers, by expressly regulating disconnection, ceasing to be a matter that only exists in the doctrine and the prescription in analogy to the right to refer to the rights of the personality. It was concluded that the Argentine legislation is serving as a vanguard with regard to the right to disconnection and protection to the psychological health of teleworkers, being ahead, therefore, of several countries, including Brazil, in regulating the right to disconnection expressly, even if it comes to bring determinations that depend on further discussions, such as the teleworker's right to, unilaterally, without prior notice, revoke the consent given to work in a telework regime, with the employer having to relocate it, under penalty of even having a kind of indirect termination.